Adaptive fuzzy-PID controller for quad-rotor MAV with mass changes - Goh, Ming Qian; Pebrianti, Dwi; Luhur, Bayuaji; Rosdiyana, Samad; Mahfuzah, Mustafa; Mohammad, Syafrullah (Springer Singapore, 2018)
Micro Aerial Vehicle (MAV) has become famous to be used in agri-cultural application such as for spraying operation, for watering plantation or spraying the pesticide, 2-D flow visualization image to measure the droplet dis-tribution and so on. Due to the need to sustain food for all human population, there is need for development of effective spraying to increase the productivity. In crop spraying, the payload changes against time is the big challenge on the development of MAV. This is because the payload change problem could affect the altitude which is the position along z-axis of the MAV. In this research, a quad-rotor MAV is used as the platform. Then, an adaptive Fuzzy-PID control-ler for the altitude control by considering payload change is presented. The per-formance of altitude control by using adaptive Fuzzy-PID controller and PID controller are validated in this research study through simulation. The adaptive Fuzzy-PID controller is successfully designed for the changing of payload. The result shows the performance of adaptive Fuzzy-PID controller is better than PID controller on quad-rotor MAV control considering payload changes.